Source-to-sink : transport of weapons-test 239+240Pu deposited in Icelandic glaciers - Biles, Celeste Marie, 1967- (2020)
Verkefnið er lokað til 01.10.2022. The contraction of glaciers worldwide transforms the abstract concept of climate change into a tangible observation. Glaciers have formed for millennia while accumulating natural and anthropogenic particles from the atmosphere. With the ablation of the glaciers in Iceland – as in the rest of the world – anthropogenic pollution is increasingly being released into downstream waters, with potential effects on the marine environment. One such pollutant is plutonium (Pu), a synthetic element produced by nuclear reactors and bomb processes globally dispersed during nuclear testing in the mid- to late-20th century. This study examines the transport of Pu, as quantified by the total activity of its two major isotopes (239+240Pu), in the surface environment. Specifically, this project focused on the Kaldalónsjökull outlet glacier of the Drangajökull ice cap in the Westfjords and the Sólheimajökull outlet glacier of the Mýrdalsjökull ice cap in the south and of the island. Sediment was collected from the system termini at both locations and analyzed using inductively coupled plasma mass spectrometry (ICP-MS). The presence of Pu activity at both sites indicates that this element has the potential to be used as a tracer for soil/sediment erosion, transport, and redistribution in surface environments on a decadal timescale. Significant differences were found in 239+240Pu activity at Kaldalónsjökull (x̅ 0.642 Bq/kg) compared to Sólheimajökull (x̅ 0.070 Bq/kg). This difference may be attributable to factors including precipitation and microclimates. The Westfjords region receives less annual precipitation and has lower yearly temperatures on average than the southern region of Iceland and has no volcanic activity, unlike southern Iceland. The 240Pu/239Pu ratio averages at the Kaldalónsjökull and the Sólheimajökull sites were 0.189 and 0.170, respectively, consistent with the Pu at both sites originating from nuclear test fallout based on previous work (Kelley, Bond, & Beasley, 1999). As ...